(untitled) (International Journal of Fine, Performing and Visual Arts, ISSN: 3006-6581, 2022)
Cultural appropriation in Western contemporary art has been a topic of considerable debate and discussion, with perspectives from different regions providing unique insights. This abstract focuses on the viewpoint from India, exploring the nuances and implications of cultural appropriation as it pertains to the intersection of Western contemporary art and Indian cultural heritage. The discourse surrounding cultural appropriation in art involves the borrowing, adoption, or imitation of elements from a culture by artists outside that culture. In the context of Western contemporary art, this phenomenon has been both celebrated as a form of cross-cultural exchange and criticized for its potential to perpetuate stereotypes and erode the authenticity of the appropriated culture.